2021
DOI: 10.3390/pharmaceutics13101543
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Therapeutic Tools for the Treatment of Chronic Wounds

Abstract: Chronic wounds develop when the orderly process of cutaneous wound healing is delayed or disrupted. Development of a chronic wound is associated with significant morbidity and financial burden to the individual and health-care system. Therefore, new therapeutic modalities are needed to address this serious condition. Mesenchymal stem cells (MSCs) promote skin repair, but their clinical use has been limited due to technical challenges. Extracellular vesicles (EVs) are particles released by cells that carry bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 213 publications
(270 reference statements)
0
26
0
Order By: Relevance
“…To explore the therapeutic potential of ADSC-EVs more accurately, BMSC-EVs and ADSC-EVs were applied, respectively to diabetic wounds, and the results demonstrated that ADSC-EVs possess the more potent pro-angiogenic activity and can promote the wound healing of diabetic ulcers ( 13 ). Considering the availability of adipose tissue and fewer ethical concerns of EVs, emerging skin regenerative studies tend to focus on ADSC-EVs to better transform to future clinical trials ( 128 ).…”
Section: Preclinical and Clinical Studies Of Adsc-evs For Skin Regene...mentioning
confidence: 99%
“…To explore the therapeutic potential of ADSC-EVs more accurately, BMSC-EVs and ADSC-EVs were applied, respectively to diabetic wounds, and the results demonstrated that ADSC-EVs possess the more potent pro-angiogenic activity and can promote the wound healing of diabetic ulcers ( 13 ). Considering the availability of adipose tissue and fewer ethical concerns of EVs, emerging skin regenerative studies tend to focus on ADSC-EVs to better transform to future clinical trials ( 128 ).…”
Section: Preclinical and Clinical Studies Of Adsc-evs For Skin Regene...mentioning
confidence: 99%
“…As discussed before, MSC-EVs could hold great promise as they are gradually recognized as effective drug delivery systems that can overcome earlier drug-stability and immunological issues [ 136 ]. This is of importance in corneal scarring/fibrosis, where the homeostatic nature of wound healing entailing of inflammation, proliferation and regeneration is disrupted [ 153 ]; meanwhile, MSC-EVs could induce a potent wound-healing process under the hypoxic and inflammatory conditions that typically characterize chronic injury [ 154 ].…”
Section: Can We Utilize Extracellular Vesicles In Treatments Regiment...mentioning
confidence: 99%
“…Clinical trials have confirmed the efficacy and safety of MSCs in wound treatment [ 154 ], but their technical utility is limited [ 155 ]. The literature on pre-clinical in vivo and in vitro studies evaluating MSC-EVs in promoting wound healing has been reported.…”
Section: Can We Utilize Extracellular Vesicles In Treatments Regiment...mentioning
confidence: 99%
“…Some cells such as MSCs are known to promote skin repair, thus MSC-derived exosomes can be used to induce skin regeneration. 94 Additionally, some milk-derived exosomes could prevent skin aging and help in wound repairing. 95 This shows that skin therapeutic agent-loaded exosomes can aid in the treatment of skin damage.…”
Section: Exosome-based Ddss In Treatment Of Various Diseasesmentioning
confidence: 99%